Meta-analysis reveals controls on oyster predation - Tedford, Kinsey N.; Castorani, Max C. N. (Frontiers in Marine Science, 2022)
Predators can have strong roles in structuring communities defined by foundation species. Accumulating evidence shows that predation on reef-building oysters can be intense and potentially compromise efforts to restore or conserve these globally decimated foundation species. However, understanding the controls on variation in oyster predation strength is impeded by inconsistencies in experimental methodologies. To address this challenge, we conducted the first meta-analysis to quantify the magnitude, uncertainty, and drivers of predator effects on oysters. We synthesized 384 predator-exclusion experiments from 49 peer-reviewed publications over 45 years of study (1977 to 2021). We characterized geographic and temporal patterns in oyster predation experiments, determined the strength of predator effects on oyster mortality and recruitment, and assessed how predation varies with oyster size, environmental conditions, the predator assemblage, and experimental design. Predators caused an average 4.3× increase in oyster mortality and 46% decrease in recruitment. Predation increased with oyster size and varied with predator identity and richness. Unexpectedly, we found no effects of latitude, tidal zone, or tidal range on predation strength. Predator effects differed with experiment type and tethering method, indicating the importance of experimental design and the caution warranted in extrapolating results. Our results quantify the importance of predation for oyster populations and suggest that consideration of the drivers of oyster predation in restoration and conservation planning may hasten recovery of these lost coastal foundation species.